Global, Regional, and National Burden of Interstitial Lung Diseases, 1990–2019: Findings from the Global Burden of Disease Study 2019 - Zeng, Qi; Jiang, Depeng (Disease and Health Research: New Insights Vol. 3, 2024)
Aims: The present study explores the global long-term changes in the prevalence, mortality, and disability-adjusted life years (DALYs) of interstitial lung diseases (ILDs); investigates the independent effect of age, period, and cohort; and projects the disease burden over the next decade. Background: Interstitial lung diseases (ILDs) can cause irreversible lung damage, resulting in an impaired quality of life, permanent physical disabilities, respiratory failure, and even death in severe types, imposing a significant burden on society. Sarcoidosis is a granulomatous disease that can affect virtually any organ, in which pulmonary involvement is highly prevalent. Methodology: Data were retrieved from the Global Burden of Disease (GBD) database 2019. The prevalence data for ILDs were primarily derived from hospital inpatient and insurance claims data. Mortality data were derived from vital registration systems, censuses, and surveys. The Joinpoint regression model was used to calculate the average annual percent change (AAPC). Age-period-cohort (APC) analysis was employed to measure the independent effect of age, period, and cohort. The Bayesian age-period-cohort (BAPC) model was used to project the global epidemiological trends until 2030. Results: From 1990 to 2019, the age-standardized prevalence (ASPR), mortality (ASMR), and disability-adjusted life years (DALYs) rate (ASDR) of interstitial lung disease and pulmonary sarcoidosis (ILD) slightly increased, whereas the ASPR, ASMR, and ASDR of pneumoconiosis decreased. High social-demographic index (SDI) regions possessed the highest ASPR, whereas low-middle SDI regions had the highest ASMR and ASDR, followed by low SDI regions in ILD. The highest ASPR, ASMR, and ASDR in pneumoconiosis were seen in the middle SDI regions. The rate ratio (RR) was high in older persons, according to the age effect. The period effect showed that whereas the RR of mortality and DALYs declined in males but climbed in women over time, the RR of prevalence increased. The more recent birth cohort had a larger relative risk (RR) in prevalence than the preceding cohort, according to the cohort effect. Over the following ten years, we predicted that ASPR, ASMR, and ASDR would be stable with little change. Conclusion: The global ILD burden was relatively severe, especially among older adults, in low and middle SDI regions, and the disease burden would remain high over the next decade. Global actions and country-specific initiatives are needed to improve this situation.